VALIDITAS DAN RELIABILITAS INSTRUMEN KECEMASAN BELAJAR MATEMATIKA PADA SISWA MADRASAH ALIYAH SWASTA - Nurmawati Nurmawati; Irma Suryani (Institut Agama Islam Negeri Padangsidimpuan, 2018)
This article aimed on finding the validity and realibility of the instrument for the students’ anxiety in learning mathematics. The method used in this research was quantitative research in survey type. The population and the sample of this research was 138 students MAS Raudhatun Najah Langsa. Techniques for collecting the data was non-test, in the type of questionnaires that has been analyzed by using Principal Components Analysis (PCA). After analyzed 31 items, 21 items showed the validity and realibilitty. The result showed that KMO-MSA values indicated that all instrument is valid and reliable. It can be used as an instrument for looking the students’ anxiety in learning especially in learning math.